O-007 Trends in mortality and morbidity after treatment of unruptured intracranial aneurysm in the United States, 2006–2016. (4th August 2020) - Majidi, S; Mehta, A; De Leacy, R; Mocco, J; Fifi, J
Abstract : Background: We aimed to assess nationally representative trends of in-hospital mortality and clinical outcome after treatment of unruptured intracranial aneurysms (UIA). Methods: The Nationwide Inpatient Sample (NIS) database from 2006 to 2016 was reviewed. Patients with unruptured intracranial aneurysm (UIA) who underwent aneurysm treatment during hospitalization were identified. Patients' demographics, comorbid conditions, length of hospital stay, rate of in-hospital mortality, discharge destination for each treatment group (microsurgical clipping and endovascular embolization). Poor clinical outcome was defined as discharge to skilled nursing facility or hospice instead of home or acute rehabilitation facility. Multivariate regression model was used to identify independent predictors of mortality and poor clinical outcome. Results: A total of 21, 609 patients with UIA were identified from 2006 to 2016. The overall rate of in-hospital mortality decreased from 0.9% in 2006 to 0.2% in 2016. Overall, 83% of the patients had favorable clinical outcome. The utilization of endovascular embolization increased from 60% in 2006 to 64% in 2016. Patients who had endovascular embolization had 3 days shorter hospital stay (1 vs 4, p<0.0001) and significantly higher rate of favorable clinical outcome compared to microsurgical clipping group (91% vs 74%, p<0.0001). Patients with age ≥ 80 years [OR (95% CI); p-value: 1.05 (1.02–1.11); p=0.03], female gender [OR (95% CI); p-value: 1.21 (1.07- 1.37); p=0.002], those with higher comorbidity index [OR (95% CI); p-value: 1.11 (1.07- 1.18); p=0.002], and patients who had microsurgical clipping [OR (95% CI); p-value: 1.29 (1.11–1.69); p: 0.021] had higher rate of poor clinical outcome. Similarly, age ≥ 80 years [OR (95% CI); p-value: 1.04 (1.01- 1.06); p=0.04], higher morbidity index [OR (95% CI); p-value: 1.52 (1.25–1.85); p<0.0001] and microsurgical clipping [OR (95% CI); p-value: 1.29 (1.11–1.69); p<0.0001] were independent predictors of mortality after treatment of the aneurysm. Conclusions: Mortality rate from treatment of unruptured intracranial aneurysm has substantially decreased in the past decade. Higher rate of morbidity and mortality is seen in patients ≥80 years old, patients with multiple comorbidities and those who were treated with microsurgical clipping. Disclosures: S. Majidi: 1; C; SNIS Foundation. A. Mehta: None. R. De Leacy: None. J. Mocco: None. J. Fifi: None.